PEMANFAATAN MEDIA LEAFLET TENTANG KESEHATAN MENTAL TERHADAP PENGETAHUAN IBU HAMIL USIA REMAJA - Susanto, Yoan Putri Praditia; Wulandari, Tasya; Hartuti, Noviyani; Salim, Agus (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan Pelamonia, 2025)
Mental health is a major aspect in determining the health of an individual, In 2019, out of every 8 people, or 970 million people worldwide lived with mental disorders, In 2020, the number of anxiety and depression disorders increased significantly, Preliminary estimates indicate an increase of 26% and 28% for anxiety disorders and major depression, respectively. Pregnant women are one of the vulnerable groups experiencing mental health problems, a woman during her pregnancy experiences many physical, psychological, and emotional changes. In Indonesia, 28.7% of all pregnant women in Indonesia reported experiencing anxiety. Objective: To determine the effect of leaflet media on mental health on increasing the knowledge of pregnant women of adolescent age. Research Methods: This study used quantitative methods through a pre-experimental approach. With One Group Pretest-Posttest Design research design. Results: Based on the results of the study before education, most participants had a poor level of knowledge (80.0%), only 20.0% had sufficient knowledge. After education, the majority of pregnant women showed an increase in good knowledge (93.3%), while 6.7% had sufficient knowledge. Statistical tests showed a P-value of 0.000 <0.05, indicating a significant difference between the pre-test and post-test. The negative Z-value also showed that the average pre-test score was lower than the post-test. Conclusion: The utilization of leaflet media is proven to have a significant positive effect in increasing the knowledge of pregnant women of adolescent age.